(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
In this study, we construct two -Step Second derivative hybrid block backward differentiation formula. The newly proposed scheme was derived based on interpolation and collocation approach. The discrete schemes were obtained from the continuous scheme. The derived method is applied to solve non-linear systems of stiff ordinary differential equations. The numerical result obtained using newly constructed method showed that it is good for stiff systems.